A abordagem CCS na formação de professores para uma escola inclusiva - Santos, Danielle Aparecida do Nascimento dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This doctoral study was conducted in the Graduate Program in Education at the Faculty of Science and Technology, Paulista State University, named after Julio de Mesquita Filho (FCT/Unesp), located on Presidente Prudente campus in São Paulo. The line of research encompasses the study of practices and formative processes in education in the areas of Information and Communication Technologies (ICT) and Teacher Education. The general goal of this research is to investigate the process of design, implementation, and assessment of the Articulating Axis Inclusive and Special Education, based on the Constructionist, Contextualized and Signified (CCS) approach. It was offered in the blended course in Pedagogy at Unesp/Univesp, as part of the teachers' initial training and in-service training. The theoretical, methodological, and practical foundations of this research underlie both inclusive and special education and the issue of training teachers for the use of ICT, guided by CSS approach, which permeated not only the whole training process, but also the spiral-shaped learning curve, based on Valente (2002). The theoretical foundation for the research rationale, development, and analysis is built on such authors as Sacristán, Zabala, Mantoan, Moraes, Morin, Gatti, García, Tardif, Nóvoa, Perrenoud, Papert, Valente, Almeida, and Schlünzen. Linked to the Support Program in Special Education at Capes, the study equips the student teachers with essentials for performing the analysis of school inclusion policies and practices and for building new pedagogical practices using technological resources when elaborating the Inclusive Lesson Plans...

A presente pesquisa de doutorado está vinculada ao Programa de Pós-Graduação em Educação da Faculdade de Ciências e Tecnologia da Universidade Estadual Paulista Júlio de Mesquita Filho (FCT/Unesp), campus de Presidente Prudente/SP, na linha de pesquisa Práticas e Processos Formativos em Educação, áreas: Tecnologias de Informação e Comunicação (TIC) e Formação de Professores. O objetivo geral é investigar o processo de elaboração, execução e avaliação do Eixo Articulador Educação Inclusiva e Especial proposto na formação inicial e em serviço de professores do curso de Pedagogia semipresencial da Unesp/Univesp com base em uma abordagem Construcionista, Contextualizada e Significativa (CCS). Os aportes teóricos, metodológicos e práticos que subsidiaram a organização da pesquisa tem correlação direta à Educação Inclusiva e Especial e à problemática da formação de professores para o uso de TDIC, segundo a abordagem CCS, que permeou toda a proposta de formação, bem como a espiral de aprendizagem baseada em Valente (2002). As bases teóricas para a fundamentação, desenvolvimento e análise da pesquisa foram subsidiadas pelas produções de autores como: Sacristán, Zabala, Mantoan, Moraes, Morin, Gatti, García, Tardif, Nóvoa, Perrenoud, Papert, Valente, Almeida e Schlünzen. Vinculada ao Programa de Apoio à Educação Especial (Proesp) da Capes, a proposta foi delineada no sentido de oferecer aos professores-cursistas elementos para a análise sobre as políticas e práticas de inclusão escolar e para a construção de novas práticas pedagógicas usando recursos tecnológicos na elaboração de Planos de Ensino Inclusivos (PEI)...
Keywords: Educação; Construcionismo social; Tecnologias de informação e comunicação; Professores - Formação; Educação especial; Inclusão em educação; Education